Phylogenetic analysis of the envelope protein (domain lll) of dengue 4 viruses - Mota, Javier (2002)
OBJECTIVE: To evaluate the genetic variability of domain III of envelope (E) protein and to estimate phylogenetic relationships of dengue 4 (Den-4) viruses isolated in Mexico and from other endemic areas of the world. MATERIAL AND METHODS: A phylogenetic study of domain III of envelope (E) protein of Den-4 viruses was conducted in 1998 using virus strains from Mexico and other parts of the world, isolated in different years. Specific primers were used to amplify by RT-PCR the domain III and to obtain nucleotide sequence. Based on nucleotide and deduced aminoacid sequence, genetic variability was estimated and a phylogenetic tree was generated. To make an easy genetic analysis of domain III region, a Restriction Fragment Length Polymorphism (RFLP) assay was performed, using six restriction enzymes. RESULTS: Study results demonstrate that nucleotide and aminoacid sequence analysis of domain III are similar to those reported from the complete E protein gene. Based on the RFLP analysis of domain III using the restriction enzymes Nla III, Dde I and Cfo I, Den-4 viruses included in this study were clustered into genotypes 1 and 2 previously reported. CONCLUSIONS: Study results suggest that domain III may be used as a genetic marker for phylogenetic and molecular epidemiology studies of dengue viruses. The English version of this paper is available too at: http://www.insp.mx/salud/index.html